Analysis Physical Characteristics of Land for Estimated Runoff Coefficient as Flood Control Effort in Comal Watershed, Central Java - Arina Miardini; Pranatasari Dyah Susanti (Forum Geografi, 2016)
Watershed conditions in Indonesia have been degraded over time, which is marked by increasing area of critical land. The vast area of critical land was evidenced to be a serious threat for watershed carrying capacity which eventually affected the hydrology imbalance in the watershed area. One among watershed with degraded lands which seriously requires priority handling is Comal watershed. The purpose of this study is to identify the physical characteristics of Comal watershed which have significant influence in determining the runoff and calculating the runoff coefficient by taking into account the parameters of watershed’s physical characteristics. The method used in this analysis is Cook method, which is done through the estimation of runoff coefficient by evaluating the parameters of slope, infiltration, vegetation cover, and drainage density.  The unit of analysis in this study is land mapping unit. Results of the four parameters are classified and the classification is done so that the scores of the runoff coefficient are figured out, while the peak discharge determination is performed by using the Rational method. The analysis showed that runoff coefficient of Comal watershed is 61.63%, which can be categorized as high. The runoff coefficients and peak discharge calculations of each sub watershed, respectively, Comal Hilir of 52.65% with peak discharge 505.68 m3/sec, Genteng of 65.04% with peak discharge 542.44 m3/sec, Lomeneng of 64.00% with peak discharge 194.23 m3/sec, Srengseng of 64.10% with peak discharge 270.46 m3/sec, and Wakung Hulu of 62.34% with peak discharge 686.64 m3/ sec. The most influential runoff coefficient factors are, respectively, infiltration rate, slope, vegetation cover, and drainage density. Flood control priority in Comal watershed should be preoccupied to increase the infiltration rate through a combination of three conservation techniques of mechanical, vegetative, and biology.